The association of microalbuminuria with clinical cardiovascular disease and subclinical atherosclerosis in the elderly: the Cardiovascular Health Study. - Cao, Jie J; Barzilay, Joshua I; Peterson, Do; Manolio, Teri A; Psaty, Bruce M; Kuller, Lewis; Wexler, Jason; Bleyer, Anthony J; Cushman, Mary (Atherosclerosis, 2006)
PURPOSE: Microalbuminuria (MA) is a risk factor for cardiovascular disease (CVD). It is not known whether this association is due to the effect of MA on the development of subclinical atherosclerosis or whether MA destabilizes subclinical atherosclerosis, leading to clinical events. METHODS: In a cross-sectional analysis we evaluated 3312 Cardiovascular Health Study participants, age >or=65 years, who had MA testing. Participants were divided into three groups: those without diabetes or hypertension (33%), those with hypertension (52%) and those with diabetes, with or without hypertension (15%). Clinical CVD was defined as presence of coronary heart disease (angina, MI, CABG, PTCA), cerebrovascular disease (stroke, TIA) and peripheral arterial disease (requiring intervention). Among those without clinical disease, subclinical atherosclerosis was defined as increased carotid artery intima-media thickness, decreased ankle arm index or increased left ventricular mass. RESULTS: In each of the three groups of participants, the adjusted odds of prevalent clinical CVD in the presence of MA was 1.70-1.80-fold increased, independent of other risk factors. MA was not associated with risk of subclinical atherosclerosis in those without hypertension or diabetes (OR 1.14 [95% CI 0.59, 2.23]), whereas it was associated with subclinical atherosclerosis in those with hypertension (OR 1.58 [95% CI 1.08, 2.30]) or diabetes (OR 2.51 [95% CI 1.27, 4.94]). CONCLUSION: In the absence of hypertension or diabetes, MA was associated with clinical CVD but not with subclinical atherosclerosis. Thus, a hypothesis may be made that the mechanism of association of MA with clinical vascular disease involves destabilization of the vasculature, leading to clinical disease.
Keywords: Aged; Aged, 80 and over; Albuminuria; Atherosclerosis; Cardiovascular Diseases; Coronary Disease; Diabetes Mellitus; Female; Humans; Hypertension; Male; Peripheral Vascular Diseases; Prevalence; Risk Factors; Stroke; United States